A Study of Future School Enrolments in Libya 1969 -1983 - K.Venkuweharye (Dirasat in Economics and Business, 1973)
Introduction Educational planning is an important phase in the development ring of any country. This assumes special importance in the case off Libya Libya has vast geographic area but only a small portion of tile inhabited. The population of the country is relatively small (about 1.8 million in 1969). The country has acquired lot of financial assets from petroleum deposits and the national wealth is likely to accelerate in the future. The government of Libya has been taking many steps to utilize its financial resources for raising the standard of living of the masses through various development projects including educational ones (Ministry of education, Document 1, 1966). It is needless to stress the importance of the school age projections of a population in its educational planning. For proper planning of education one needs to plan for future buildings, teachers, laboratories etc., all of which depend on the future student population. In the present paper, a set of projections for Libya are worked out for primary, preparatory and secondary schools for the period 1969-83. The work of obtaining future school age population by age or class poses a number of problems most of them originating from either lack of data or errors in the existing data. For these reasons the projections of future school age population should be interpreted with care.